STRENGTHENING SUPERVISION OF ENFORCEMENT OF CIVIL SERVANTS' DISCIPLINE LAW AT THE MINISTRY OF FINANCE - Suatmaji Purwanto, Bayu (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
Government agencies are required to enforce discipline on civil servants and carry out various efforts to improve discipline. Disciplinary law enforcement aims to create civil servants with moral integrity, professional, and accountable, as well as productive and with integrity. The formulation of the problem in this study are: (1) How is the regulation of law enforcement for civil servant discipline?; (2) How are the implementation and obstacles in implementing the discipline law enforcement for Civil Servants?; and (3) How to strengthen the supervision of civil servant discipline law enforcement?. The method used in this study is an empirical normative legal approach. The results of the study indicate that there are still deviations from the regulation of civil servant discipline law enforcement, This is influenced by several factors, namely abuse of authority, conflict of interest, leadership, staffing officers who do not receive adequate information in decision making, as well as external pressure. Strengthening supervision can be done by strengthening institutions, for example by establishing an independent supervisory board that is directly responsible to the Minister of finance, increasing the competence of investigative auditors, expanding networks of cooperation or partnerships with other law enforcement officials in the context of increasing mutual understanding, as well as expanding administrative efforts.